Hubungan Beban Angkut Terhadap Kejadian Kifosis Pada Buruh Panggul - Tiffany Gita Yunilia Sari; Nuryani Sidarta (Jurnal Biomedika dan Kesehatan, 2022)
BackgroundOccupational diseases that are often found in the porter (transport worker) are related with the changes in the structure of the spine. Work load, length and duration of work are factors that affect the spine curve. This study aims to see whether there is a relationship between those factors with the incidence of kyphosis among the workers. MethodsThe study used an observational study with a cross-sectional design that included 51 male workers aged 15-65 years in Sumbawa Regency. Sample selection is done in consecutive random sampling. Workers who had conditions such as a history of spinal surgery, spinal fractures, spinal tumors, spinal infections and osteoporosis were not included in the study. The curve of thoracic kyphosis is measured by flexible ruler. The calculation of the degree uses a standard and predetermined kyphosis index formula. Data on carrying loads, duration of work per day and length of work is obtained from the results of questions and answers with workers. The Fisher test was used as a statiscal analysis with a p value <0.05. ResultsIn this study, 60.8% of the porter had worked for more than 10 years and most had a carrying load of > 40 kg with the duration of work more than 8 hours per day. Measurements of the curvature of the vertebrae found that 35 people (68.6%) had normal curves followed by 16 people (31.3%) had kyphosis. Statistical test results with Fishertest found a significant relationship between carry load (p=0.003), duration of work (p=0.047) and working period (p=0.037) with kyphosis. ConclusionsThere is a significant relationship between the load of transport and the incidence of kyphosis in transport workers. The length of work per day and working period also have a significant influence on the efficacy of kyphosis.